Biogas Production from Co-Digestion of Pretreated Spent Grounds Coffee with Cow Dung (Manure) by Batch and Fed-Batch Fermentation - Sohsalam, Prapa; Charoenthanaphat, Thuntidee; Pawongrat, Ratchapol (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2023)
This research aimed to investigate the biogas production from co-digestion of pretreated spent ground coffee and cow manure in batch and fed-batch fermentation processes at 35°C. The ratio of pretreated coffee grounds to cow manure was 4:1 representing 10% of the total solids solid material. The experimental results of the batch fermentation process were showed that the carbon-to-nitrogen ratio (C:N ratio) of coffee grounds with cow manure at 24:1 has maximum biogas yield of 44.50 milligram per gram volatile solids (ml/g-VS). Therefore, this optimum C:N ratio (24:1) was used for biogas production in a semi-batch fermentation process. However, when adding organic substances to the system every 2 days, which was 3 times for 15 days, the maximum biogas content was Type 1 (the maximum accumulated biogas was 38.00 ml/g-VS) and the amount of methane and carbon dioxide were 20.12% and 6.47%.